2020
DOI: 10.2147/jaa.s236609
|View full text |Cite
|
Sign up to set email alerts
|

<p>Real-World Effectiveness of Mepolizumab in Patients with Severe Asthma: An Examination of Exacerbations and Costs</p>

Abstract: Rationale: Results from clinical trials in patients with severe eosinophilic asthma have demonstrated that mepolizumab is well tolerated and is associated with improved asthma control as evidenced by reductions in both exacerbations and maintenance oral corticosteroid use, and improvements in lung function, asthma control, and quality of life. However, real-world data are lacking on the impact of mepolizumab treatment. Objective: To assess the effect of mepolizumab treatment on the rate of asthma exacerbations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 20 publications
(31 reference statements)
2
34
2
2
Order By: Relevance
“…As expected, our results confirmed the effectiveness of the drug in terms of reduction of exacerbation rate, and consequently need for systemic steroids, and also in terms of improvement of asthma control and functional parameters. There have been many reports in the literature on the efficacy of mepolizumab from RCTs and real-life studies [22, 23]. Our study contributes to the topic, confirming that mepolizumab is very effective in reducing respiratory symptoms, the number and severity of exacerbations, and OCS intake, enabling significant health gains in patients with severe eosinophilic asthma.…”
Section: Discussionsupporting
confidence: 74%
“…As expected, our results confirmed the effectiveness of the drug in terms of reduction of exacerbation rate, and consequently need for systemic steroids, and also in terms of improvement of asthma control and functional parameters. There have been many reports in the literature on the efficacy of mepolizumab from RCTs and real-life studies [22, 23]. Our study contributes to the topic, confirming that mepolizumab is very effective in reducing respiratory symptoms, the number and severity of exacerbations, and OCS intake, enabling significant health gains in patients with severe eosinophilic asthma.…”
Section: Discussionsupporting
confidence: 74%
“…11 The fact that we observed broadly similar results in a real-world setting highlights the robust OCS-sparing effect associated with mepolizumab and is also consistent with results from several other smaller, real-world studies. [15][16][17][18] We also found that mepolizumab treatment was associated with a 45.5% reduction in the annualized rate of asthma exacerbations and 60% reduction in the annualized rate of exacerbations resulting in hospitalization. The reductions we observed are broadly in line with those reported in smaller real-world studies, [15][16][17][18] and with results from the SIRIUS study where, despite receiving a reduced OCS dose, patients in the mepolizumab group had a relative reduction of 32% in the annualized rate of exacerbations compared with those in the placebo group.…”
Section: Discussionmentioning
confidence: 52%
“…[15][16][17][18] We also found that mepolizumab treatment was associated with a 45.5% reduction in the annualized rate of asthma exacerbations and 60% reduction in the annualized rate of exacerbations resulting in hospitalization. The reductions we observed are broadly in line with those reported in smaller real-world studies, [15][16][17][18] and with results from the SIRIUS study where, despite receiving a reduced OCS dose, patients in the mepolizumab group had a relative reduction of 32% in the annualized rate of exacerbations compared with those in the placebo group. 11 Our data also support the efficacy of mepolizumab observed in other clinical trials (using the licensed dose, 100 mg subcutaneously), where reductions of 53-58% in the rate of all exacerbations versus placebo and 69% in the rate of exacerbations requiring hospitalization versus placebo were reported.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…However, several studies have reported similar outcomes in the realworld setting, suggesting that the results are consistent and likely to be generalizable. (50)(51)(52)Lastly, some of the model inputs such as the local mortality rate from asthma exacerbations at the ED (24) and utility decrements due to asthma exacerbations (25) were informed by data older than 5 years. Nonetheless, these inputs are likely to still be valid as they were verified by local clinical experts, and similar utility decrements were used in the CEAs conducted by Whittington et al (2017) and NICE TA431 (2017).…”
Section: Accepted Manuscriptmentioning
confidence: 99%